Exploring hepatitis E virus seroprevalence and associated risk factors among the human population in Tandil, Buenos Aires, Argentina - Rivero, Mariana Alejandra; Arce, Lorena Paola; Gutiérrez, Silvina Elena; Tisnés, Adela; Passucci, Juan Antonio; Silva, Julia Analia; Barón Prato, Ayelén; Sánchez, Florencia; Matias Brancher, Julia; Estein, Silvia Marcela; Vizoso-Pinto, María Guadalupe (Frontiers in Public Health, 2023)
Background: Hepatitis E virus (HEV) infection is a common cause of acute clinical hepatitis worldwide and is emerging as a disease in Argentina. It is primarily transmitted through contaminated water and food, following the fecal-oral route. Furthermore, is a zoonotic disease with swine as the primary reservoir. Prevalence of HEV infection in humans in several regions of Argentina remains unknown. Objectives: i) Determine the seroprevalence of HEV among the human population in Tandil, Buenos Aires, Argentina; ii) Evaluate its association with demographic, socioeconomic and other risk exposures variables, and iii) Describe and analyze spatial patterns related to HEV infection. Methods: From August 2020 to July 2021, serum samples were collected from 969 individuals aged 1-80 years. Seroprevalence and 95% Confidence Interval was determined.To assess the factors associated with the presence of anti-HEV antibodies, associations between the variables and seropositivity were evaluated through bivariate and multivariate analysis. Spatial scanning for clusters of positivity was carried out. Factors associated with these clusters were also assessed. Results: Anti-HEV antibodies were detected in 4.64% (IC 95% 3.27-6.02) of samples. Dark urine was associated with seropositivity (p=0.02). Seropositivity was linked with the presence of natural water courses near their households (p=0.02); the age (p =0.04); and previous travel to Europe (p= 0.04). A spatial cluster of high rates of seropositivity was detected, coinciding with an area with natural water courses (statistically associated with the cluster), high risk of flooding and the proximity of a sewage treatment plant. A spatial cluster of low rates of HEV seropositivity was detected, with male sex, and greater distance of the households to water courses inversely associated within the low rate cluster. Discussion and conclusion: This study is the first study to investigate the prevalence of HEV in the population from Tandil, Buenos Aires, Argentina. Considering HEV infection in the differential diagnosis in individuals presenting acute hepatitis is highlighted. The incorporation of HEV testing into blood screening policies should be mandatory. Factors related to the infection and spatial patterns of high and low risk were determined, and should be considered when implementing specific preventive measures.